Leadership Dynamics for Sustainable Entrepreneurship: Driving Innovation in Business Models - Bayuningrat Bayuningrat; Aghnia Nadhira Aliya Putri; Fadrian Dwiki Maulanda (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2024)
The integration of Environmental, Social, and Governance (ESG) principles has become increasingly critical for sustainable business practices, particularly in emerging markets like Indonesia. This study examined how leadership dynamics influenced the implementation of ESG practices among Indonesian business leaders by analyzing their motivations, challenges, and outcomes in fostering environmental stewardship, driving innovation, and aligning business operations with broader societal goals across various industries. The research employed a qualitative approach, utilizing focus group discussions (FGDs) with leaders from nine prominent companies spanning sectors such as environmental technology, manufacturing, retail, and agribusiness. Data collection included both primary data from FGDs and secondary data from company reports and industry analyses. A three-stage data analysis process was conducted: (1) a thematic analysis to identify leadership approaches and ESG strategies; (2) a comparative analysis to assess sector-specific challenges and solutions; and (3) data triangulation to validate findings across multiple sources. The findings highlight the critical role of transformational, strategic, and eco-leadership styles in driving ESG adoption. Despite industry-specific challenges, shared themes emerged regarding environmental stewardship, social responsibility, and ethical governance. The results underscore the strategic advantages and societal benefits of ESG integration, demonstrating that effective leadership is essential for achieving sustainable business growth and long-term success in Indonesia’s emerging market context.